Censorship in literature education: Background and guidelines to facilitate the discussion of controversial youth literature - Judith Elizabeth Vos; Janneke De Jong-Slagman; Dorit Barchana-Lorand (Perspectives in Education)
Youth literature can be regarded as an important educational tool. However, controversial issues in youth literature become more prominent and the different opinions (internationally and individually) on such issues place the focus more on censorship. This article aims to provide an overview and analysis of the discourse on censorship in literature. Language teachers remain the most dominant role players in schools to make the correct text choices in promoting reading. Our study proposes a critical pedagogical approach to controversial issues in youth literature. We offer guidelines that language teachers can use in the classroom to facilitate the discussion of controversial issues in youth literature in a self-directed manner with learners.